(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Dentin hypersensitivity may be defined as pain arising from exposed dentin. The relationship between dentin hypersensitivity and the patency and Microleakage through dentinal tubules has been established in vitro. Currently the most accepted mechanism of nerve activation associated with dentin hypersensitivity appears to be hydrodynamic in nature. Objectives: The concept of tubule occlusion as a method of dentin desensitization is a logical conclusion of the hydrodynamic theory. Methods: Forty two human maxillary anterior teeth were selected, the crowns were cut away at the CEJ, the root canals prepared, cleaned and filled then the coronal access closed with zinc phosphate cement. The specimens were randomly divided into four groups, two of them experimental A and B and two controls C (positive) and D (negative). All the specimens were coated with sticky wax except the ring that had cementum removed while the negative control specimens were entirely coated with sticky wax. All the specimens were stored in human saliva which was changed daily for 21 days with daily brushing of specimens of group A with a Sensodyne tooth paste (that with active ingredient Strontium chloride). At the end of the 21 days, the specimens were immersed in pelikan ink for three days then the sticky wax was removed, after that the teeth were cleared to make them transparent to provide a three dimensional assessment of dye penetration. The teeth were subjected to linear dye penetration measurement and scanning electron microscope analysis to investigate whether Sensodyne with Strontium chloride occlude dentinal tubule orifices. Results:Strontium chloride, the active ingredient of Sensodyne tooth paste has a tubule occluding property which may indicate a therapeutic potential in vivo. Also scanning electron microscopic analysis revealed presence of deposits in and around the tubular orifices. Conclusion: Sensodyne with strontium chloride proved effective (in vitro) in occluding the orifices of patent dentinal tubules. Keywords :Dentin hypersensitivity, Dentinal tubules occlusion, Sensodyne with strontium chloride.